2011
DOI: 10.1371/journal.pntd.0000926
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I, MDA5 and TLR3 Synergistically Play an Important Role in Restriction of Dengue Virus Infection

Abstract: Dengue virus (DV) infection is one of the most common mosquito-borne viral diseases in the world. The innate immune system is important for the early detection of virus and for mounting a cascade of defense measures which include the production of type 1 interferon (IFN). Hence, a thorough understanding of the innate immune response during DV infection would be essential for our understanding of the DV pathogenesis. A recent application of the microarray to dengue virus type 1 (DV1) infected lung carcinoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
233
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(252 citation statements)
references
References 45 publications
9
233
0
6
Order By: Relevance
“…The anti-DV response was diminished when an antagonist was used to block the P2X 7 receptor (Fig. 3C), suggesting that full anti-DV activity by gd T cells requires activation checkpoints that involve two independent pathways of danger recognition: IRF-dependent pathways that lead to secretion of type I IFN (e.g., sensing of viral RNA by TLR3 and RIG-like receptors) (48,49) and the detection of extracellular ATP (e.g., released as a result of cell damage) with subsequent inflammasome activation (50). Reconstitution experiments demonstrated that CD16 + monocytes have a greater ability, on a per-cell basis, to augment the IFN-g response of gd T cells to DV-infected DC compared with CD14 + monocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-DV response was diminished when an antagonist was used to block the P2X 7 receptor (Fig. 3C), suggesting that full anti-DV activity by gd T cells requires activation checkpoints that involve two independent pathways of danger recognition: IRF-dependent pathways that lead to secretion of type I IFN (e.g., sensing of viral RNA by TLR3 and RIG-like receptors) (48,49) and the detection of extracellular ATP (e.g., released as a result of cell damage) with subsequent inflammasome activation (50). Reconstitution experiments demonstrated that CD16 + monocytes have a greater ability, on a per-cell basis, to augment the IFN-g response of gd T cells to DV-infected DC compared with CD14 + monocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In some cell types, polyIC can induce IFN␣/␤ via activation of TLR3 at the cell surface or in the endosomes (11,38,39) other responses that are similar to those evoked by viral infection via cytoplasmic dsRNA receptors (32,40). mESCs were unresponsive to polyIC that was directly added to the medium, likely due to the very low level expression of TLR3.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that MDA5 and RIG-I play primary roles in mediating viral RNA-induced IFN␣/␤ expression in the cytoplasm (11,39), although PKR also contributes to and modulates this process (13,14). Because MDA5 is expressed at a negligible level in mESCs, it is conceivable that PKR and/or RIG-I may mediate the effects of transfected polyIC.…”
Section: Discussionmentioning
confidence: 99%
“…25 We further examined the expression of pattern recognition receptors involved in DV-induced inflammatory cytokine releases, such as Toll-like receptors (TLRs), [26][27][28] …”
Section: Differential Phenotypes Of Gm-m and M-mmentioning
confidence: 99%